Ethnoscience-Quizizz test to measure problem-solving skills: a Rasch analysis - Khoirun Nisa; Nadi Suprapto; Mohd Zaidi Amiruddin; Eka Putri Dian Nata Sari; Bilqisth Dwi Athiah (International Journal of Evaluation and Research in Education (IJERE), 2024)
Problem-solving skills (PSS) are essential for students to face challenges in the 21st century. Based on PISA results, the PSS of Indonesian students are in a low category. Not only that, a few assessments of PSS have been developed. This study aims to analyze the quality of the ethnoscience-Quizizz test (EQT). The research method used is R&D with the ADDIE model. The data analysis technique was based on the Rasch analysis using the Ministep software. The item and person reliability are 0.9 (good) and 0.40. Cronbach’s alpha has a value of 0.53. The MNSQ-ZSTD infit-outfit score is in a suitable category. Each item is relatively accurate and do not have DIF. In addition, the EQT is suitable to measure students’ PSS because it has passed the criteria. The EQT incorporates indicators for problem-solving, making it appropriate for 21st-century learning with an ethnoscience “Kerapan Sapi” problem context. Future studies can use this problem-solving test to determine the profiles of students’ problem-solving abilities using Rasch analysis.